HUBUNGAN DUKUNGAN AYAH DENGAN STATUS IMUNISASI BALITA DI DESA OEFAFI DALAM WILAYAH KERJA PUSKESMAS OESAO KABUPATEN KUPANG - Nofiyanti Paulus (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2018)
Immunization as a preventive way is used to prevent Tuberculosis, Diphtheria, Pertussis, Polio, Hepatitis B, and Measles, through the provision of immunity should be given continuously, thoroughly and implemented according to standards it can so as to provide health protection. The a in of this study was to determine the correlation between father’s support and immunization status of children under five village in puskesmas Oesao Kabupaten Kupang. The design used in this research correlation with cross-sectional design. The independent variable is father’s support and the dependent variable is immunization status. The sample taken is total using total sampling technique with 53 respondents. Data collecting technique used in this reseacrh is questionnaire. The results showed that there is no significant correlation between father’s support and immunization status of children under five indicated by p = 0,475> 0,005, r = 0,100 then H1 is rejected and H0 is accepted, it means there is no correlation between father’s support and childrenunder five immunizationstatus. The researcher the nursing department of puskesmas to improve that any immunization officer must provide health education and family involved in disseminating the immunization program that targets health center program coverage can be achieved through collaboration with community health worker. Keywords: Father's Support, Children Under Five Immunization Status